2024
DOI: 10.3390/scipharm92020017
|View full text |Cite
|
Sign up to set email alerts
|

Semaglutide as a Possible Calmodulin Binder: Ligand-Based Computational Analyses and Relevance to Its Associated Reward and Appetitive Behaviour Actions

Giuseppe Floresta,
Davide Arillotta,
Valeria Catalani
et al.

Abstract: Semaglutide, a glucagon-like peptide-1 (GLP-1) receptor agonist, has gained considerable attention as a therapeutic agent for type 2 diabetes mellitus and obesity. Despite its clinical success, the precise mechanisms underlying its pharmacological effects remain incompletely understood. In this study, we employed ligand-based drug design strategies to investigate potential off-target interactions of semaglutide. Through a comprehensive in silico screening of semaglutide’s structural properties against a divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Furthermore, both the beneficial effect of GLP-1 RAs on psychopathological aspects (e.g., improved mood) [ 21 , 55 ] and the significant weight loss-related improvement in one’s appearance [ 22 , 56 , 57 , 58 ] could also be hypothesized as being significant factors contributing to reduced drug consumption levels. Previous research has also suggested both direct and indirect effects of GLP-1 RAs on craving, pleasure circuits, and extended networks of substance abuse-related receptor mechanisms [ 6 , 59 ]. Finally, the direct adverse effects of GLP-1 RAs in the context of alcohol abuse are likely to be mainly of gastroenterological relevance [ 60 ], hence acting as anti-addictive/aversive stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both the beneficial effect of GLP-1 RAs on psychopathological aspects (e.g., improved mood) [ 21 , 55 ] and the significant weight loss-related improvement in one’s appearance [ 22 , 56 , 57 , 58 ] could also be hypothesized as being significant factors contributing to reduced drug consumption levels. Previous research has also suggested both direct and indirect effects of GLP-1 RAs on craving, pleasure circuits, and extended networks of substance abuse-related receptor mechanisms [ 6 , 59 ]. Finally, the direct adverse effects of GLP-1 RAs in the context of alcohol abuse are likely to be mainly of gastroenterological relevance [ 60 ], hence acting as anti-addictive/aversive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, treatment with semaglutide is also related to reductions in substance use or compulsive behaviors other than eating [ 97 ]. Alterations in dopaminergic pathways in the preclinical model and in human brains both contribute to substance misuse and play a role in compulsive behaviors [ 98 , 99 ], leading to the hypothesis that GLP-1 RAs can act on several factors influencing different maladaptive behaviors, manifesting cross-cutting effects on behavioral and non-behavioral addictions [ 59 ]. The overlap between food and substance cravings at a neural level shows the intricate connection between brain reward pathways.…”
Section: Discussionmentioning
confidence: 99%